Psychological tests for expectant parents and young children in the Nordic countries: A review of the evidence - Peltonen Kirsi; Kurki Marjo; Reedtz Charlotte; Kaiser Sabine; Rasmussen Lene-Mari P; Merikukka Marko; Rye Marte; Laajasalo Taina; Kyrrestad Henriette; Karjalainen Piia; Pettersen Susann Dahl; Eng Helene; et al. (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
The aim of this article is to review the psychometric properties of the psychological tests that are being used in the Nordic countries during pregnancy and the child's first two years of life. A systematic literature search was performed for 33 identified tests routinely used in health care, using specific review databases as well as PsycInfo, Embase and Medline. The trained authors conducted an overall assessment of quality for each test which was then verified by the editors. A total of 12% of the tests were rated at Level 1 'Low level of quality', 61% at Level 2 'Some evidence of Quality', 15% at level 3 'Good level of Quality' and 12% at Level 4 'High level of quality'. This indicates that the evidence for the psychometric properties is insufficient for many tests used in the Nordic countries for this purpose